Germanic and Slavic Paganisms: Security Threats and Resiliency - Aitamurto, Kaarina (Religion at the Boundaries Series, 2024)
Cover -- Contents -- Biographies -- Acknowledgements -- Glossary of terms and abbreviations -- Introduction -- Part I Shifting foundations - How the core features of Paganisms are changing -- 1 The rise of inclusive heathenry: How movements respond to political currents Jennifer Snook -- 2 Deradicalization of Czech Pagan black metal: Decrease of militant anti-Christianity and far right tendencies Miroslav Vrzal -- 3 Innangard: Folkish-enabling concepts in inclusive Heathenry Richard Blackett and Denise Vast -- 4 Narratives in the dialogue of the use and abuse of rune magic in contemporary Paganisms Angie Padilla -- 5 Grandsons of Dazhbog and Svarog: Ridnovirs in the socio-cultural space of Ukraine Oksana Smorzhevska -- 6 Forget history: Censuring identities within Polish contemporary Paganism Mariusz Filip -- 7 The changing faces of Paganisms in Slavic nations Kaarina Aitamurto and Ross Downing -- Part II Prescient threats - Realities of social and real violence from Pagan extremism -- 8 When Perun goes to war: An overview of Pagan ethos and rituals in the Ukrainian army Adrien Nonjon -- 9 Locating the role of Paganism in far right groups on the Russian socio-political landscape Victoria Hudson -- 10 Selective Frith: Meeting Heathen world-building in English/Welsh prisons Richard McDonald -- 11 AllatRa and Creative Society: Cult-like Slavic Pagan off-shoot Jakub Ludvík and Pavol Kosnáč -- 12 Developing CT awareness and negotiating sensitivity to Paganisms Andrew Pardy -- 13 Ridnovirstvo in the Ukrainian context: An objective perspective and identification of potential threats Taras Tarasiuk -- 14 The research-political vegvísir: Navigating contemporary Pagan and far right appropriations of Viking studies Saga Rosenström and Barbora Žiačková -- Part III Innovations: New approaches indicating innate solutions.